TANGGAPAN PENGGUNA TERHADAP KONTRIBUSI BAHAN AJAR IPAS V SD BEBASIS STREAM SEBAGAI CAPAIAN PROFIL PELAJAR PANCASILA P3 - Achmad Fanani; Dian Kusmaharti; Arif Mahya Fanny; Zahra Maulidha; Fifi Hidayatul Ilmia; Meinda Samudra Utari (Postgraduate, University of Mataram, 2025)
Pancasila Student Profile (P3) is designed to improve the quality of education in Indonesia. This study inserts the R (Religion) element in the STEAM approach into the STREAM approach in the teaching materials of IPAS V SD. Said that this study aims to describe the responses of users (teachers and prospective teachers) to the contribution of STREAM-based IPAS V SD teaching materials as a support for P3 achievements. The research method used is descriptive quantitative, using user responses as data collection. The content and competencies of students in this teaching material are packaged and presented in the form of activities related to aspects of Science, Technology, Religion, Engineering, Art and Mathematics. Which is integrated in learning. With the light of knowledge and wisdom of learning as well as a short comic of gratitude for Allah's blessings and greatness on each topic related to the content of the chapter as a form of strengthening the character education of students. The results of the study concluded that user responses to STREAM-based IPAS V SD teaching materials can contribute as a support for P3 achievement with a score of 82.97%, the predicate is very feasible.